Formation of Ion Cluster During Bombardment of Ice Surface by Low-Energy Ar+ Ions (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The process of sputtering of ice film with doped Na+ ions covering the Au (111) surface was studied. It was found that sputtering of a large ion cluster is observed due to the polarity of ice during ion bombardment. The size of the sputtered ion cluster depends on the polarization of water molecules. At the bombardment by Ar+ ions, it was found that in the presence of a Na+ ion, an ice cluster consisting of several water molecules is formed on the ice surface. The results obtained are of great interest when cleaning metal surfaces from various types of films.